2023
DOI: 10.1021/acs.macromol.2c02200
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Comonomer-Directed Epitaxial Nucleation and Growth of β-Nucleated Isotactic Polypropylene

Abstract: We present a molecular-level investigation of the epitaxial crystallization of β-nucleated isotactic polypropylene associated with the minor and local topographic modification at the interface, i.e., the inclusion of an ethylene comonomer. The experimental results show that the relative fraction of β-crystal (K β) decreases progressively with increasing the amount of ethylene comonomer, which originates from a simultaneous reduction in the β-nucleation ability of a β-nucleating agent (N,N′-dicyclohexyl­terepht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This temperature range is widely reported to be about 100−140 °C for PPH. 9,18,22,42 Despite what happens to T** being unclear to the authors' knowledge, T* has been reported to decrease in PPR. 19,20 Varga et al 21 have observed a lowering of T* and attributed it to a higher deceleration of G β than G α with increasing defect fraction.…”
Section: Growth Behavior Of Dcht-nucleated Ippsmentioning
confidence: 77%
See 3 more Smart Citations
“…This temperature range is widely reported to be about 100−140 °C for PPH. 9,18,22,42 Despite what happens to T** being unclear to the authors' knowledge, T* has been reported to decrease in PPR. 19,20 Varga et al 21 have observed a lowering of T* and attributed it to a higher deceleration of G β than G α with increasing defect fraction.…”
Section: Growth Behavior Of Dcht-nucleated Ippsmentioning
confidence: 77%
“…16−18 For example, the introduction of N,N′-dicyclohexylterephthalamide (DCHT) can induce a large amount of β-phase in PPH with k β exceeding 0.8 15 while the values of k β decreased progressively to 0.70, 0.53, and 0.07 in PPR with ethylene contents of 0.34, 0.60, and 3.11 mol %, respectively. 18 Regarding the varying k β with the matrix chain structure, it is now widely accepted that the insertion of comonomer in PPR disrupts the chain regularity, leads to an unfavorable β-growth kinetically, and results in decreased k β . 19−21 Generally, the αand β-phases in iPP have different temperature-dependent growth rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymorphism in semicrystalline polymers has considerable influence on their physical properties. Isotactic polypropylene ( i- PP) is a typical example with four common polymorphs: α-, β-, γ-, and δ-forms, , and a recently reported ε-form . All these crystal forms contain only one chain conformation, i.e., the threefold helix with a 6.5 Å repeat.…”
Section: Introductionmentioning
confidence: 99%